Penggunaan Ekoenzim pada Tingkat Pertumbuhan Bayam Cabut (Amaranthus viridis) - Yewi Eltiya; Nirwana Nirwana; Deni Parlindungan; Mellyta Uliyandari; M. Sutarno (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Spinach is one of the most common types of green plants in Indonesia. This one plant is a type of vegetable that is easily processed for everyday food, from soup, pecel, gado-gado (Indonesian food), also chips. Amaranthus viridis also known as spinach pull out. In this study, observed the growth of spinach plants with ecoenzyme treatment. The treatment groups were: A (1.5% ecoenzyme), B (3% ecoenzyme), C (4.5% ecoenzyme), D (6% ecoenzyme), E (control/without treatment), F (NPK/ chemical fertilizer). Parameters observed were height, stem diameter, number of leaves, leaf diameter, wet weight and color. This type of research is experimental research and ANOVA data analysis techniques. The duration of the study was 27 days with 9 scheduled observations. Measurements were made in the afternoon, with reference to the observation parameters of stem height, leaf diameter, number of leaves, leaf diameter, leaf color and wet weight. The results of the observations showed that the ecoenzyme treatment was no better than the control and the NPK fertilizers showed that the height, stem diameter, number of leaves, leaf diameter, wet weight and color tended to be smaller. The conclusion of giving ecoenzymes at doses of 1.5%, 3%, 4.5% and 6% does not accelerate and tends to inhibit the growth of spinach (Amaranthus viridis).